Has continued exposure to banana Xanthomonas Wilt worsened farmers’ welfare over time? Evidence from banana-producing households in Uganda - Mbabazi, Esther Gloria; Kikulwe, Enoch Mutebi; Kyanjo, Joseph Lule; Mulumba, Nasser; Kato, Edward; Gotor, Elisabetta (Canadian Center of Science and Education, 2021)
The livelihoods of millions of banana-farming households have been affected by Banana Xanthomonas Wilt (BXW) in Uganda for nearly two decades. The disease has no known cure, all banana cultivars grown are susceptible to it and it is endemic in all banana-producing regions in the country. This study analysed the long-term impact of the disease on the livelihoods of banana-producing households. Using a balanced panel dataset of 1,056 households, which were visited in 2015 and revisited in 2018, provides the opportunity to empirically measure the long-term consequences of the disease on farmers’ economic wellbeing in the four major banana growing regions in Uganda. We find striking results pertinent to disease incidence, success in disease management, household income and poverty when deploying BXW control practices. Although the disease has remained present in farmers’ fields, there is a significant reduction in household poverty levels. Results show that some farmers expanded the production of beans and coffee without encroaching on their banana plantations. Increase in bean production was largely through intercropping. Investment in coffee was constrained by land ownership, hence only a viable venture for the wealthy farmers who own bigger pieces of land. Land-poor farmers continued to rely on bananas for their livelihoods. Consistent participation in disease management training significantly influenced adoption of the cultural control practices. Consequently, farming households that systematically adopted these practices were able to maintain low levels of disease incidence, improve productivity by 438 kg/ha/year and increased their daily and annual household income by US$1.75 and UGX 2.383 million (US$648), respectively. The findings suggest that banana is an important crop to smallholder farmers and expansion into other cash crops requires bigger resource outlays, and that despite continued exposure to BXW, farmers’ income increased over time. Farmers should continuously and systematically use the recommended control practices to avoid BXW resurgence and, consequently, a reduction in their income.